منهجية DCA للتخطيط الاستراتيجي المؤسسي - أبو طبيخ، ليث شاكر محسن; الياسري، أسعد عبدالعزيز مرزه (جامعة الكوفة - كلية الإدارة والاقتصاد, 2022)
يسعى هذا البحث إلى دراسة العلاقة والأثر لمنهجية ((DCA على التخطيط الاستراتيجي المؤسسي كأداة من أدوات وأساليب التخطيط الاستراتيجي الحديثة وكيفية استخدامها في رسم الخطط المستقبلية الفاعلة والمؤثرة للمنظمات في عالم الأعمال عمومًا ومنظمات القطاع العام والمؤسسات الحكومية خصوصًا. استمد البحث مادته العلمية والعملية من إعداد خطة استراتيجية بكامل عناصرها على أرض الواقع لأحدى المؤسسات الحكومية الخدمية (مديرية طرق وجسور كربلاء المقدسة) التي أعتمدها الباحثان كعينة بحثية ونموذج تطبيقي لاستخدام منهجية ((DCA للتخطيط الاستراتيجي المؤسسي، يعتمد البحث المنهج الوصفي التحليلي، اشتملت عينة البحث على كافة الموظفين والموظفات من حملة شهادة البكالوريوس فما فوق من العاملين في تلك المديرية في جميع الشعب والوحدات الإدارية فيها والذين تم استبيان رأيهم بواسطة أداة القياس (الاستبانة) التي تم إعدادها وتحكيمها للحصول على البيانات اللازمة لدراسة هذين المتغيرين بأبعادهما المتعددة. استخدم البحث العديد من الأدوات والوسائل الإحصائية لتحليل البيانات للحصول على النتائج، حيث تم استخدام برنامج SPSS V.24)) وبرنامج (SmartPLS V.3.2.2) للقيام بوصف وتحليل البيانات التي تم الحصول عيلها من العينة المبحوثة لقياس وتشخيص العلاقات ما بين متغيرات وأبعاد البحث والاختبارات الإحصائية اللازمة لإنجاز البحث. توصل البحث إلى عدة استنتاجات أبرزها إن استخدام المنهجيات الحديثة للتخطيط الاستراتيجي المؤسسي مثل منهجية (DCA) يساهم بشكل كبير وواضح وملموس في تطوير أداء المنظمات المختلفة كونها تتميز بقدرتها الفائقة على التشخيص وتحليل المعلومات التي يتم جمعها بطريقة تفاعلية مبتكرة ولما تستند إليه من تقنيات ومهارات ومفاهيم متنوعة وفاعلة وتعدد في مخرجاتها جعلها تتميز عن غيرها من المنهجيات وأساليب التخطيط التقليدية الجامدة. أما أهم التوصيات فكانت مطالبة الإدارات العليا للمنظمات المختلفة باستثمار الوسائل والأدوات الملائمة والعمل وفق المنهجيات الحديثة للتخطيط الاستراتيجي مثل منهجية (DCA) والاعتماد عليها في إعداد خططها الاستراتيجية. This research seeks to study the relationship and impact of the (DCA) methodology on institutional strategic planning as a tool and methods of modern strategic planning and how to use it in drawing effective and influential future plans for organizations in the business world in general and public sector organizations and government institutions in particular. The research derived its scientific and practical material from preparing a strategic plan with all its elements on the ground for one of the government service institutions (The Directorate of Karbala’s Holy Roads and Bridges) which the researchers adopted as a research sample and an applied model for using the (DCA) methodology for institutional strategic planning. All male and female employees who hold a bachelor’s degree or above who work in that directorate in all the divisions and administrative units in it, whose opinion was surveyed using the measurement tool (the questionnaire) that was prepared and judged to obtain the data necessary to study these two variables in their multiple dimensions . The research used many tools and statistical means to analyze the data to get the results, where the (SPSS V.24) and (SmartPLS V.3.2.2) program were used to describe and analyze the data obtained from the researched sample to measure and diagnose the relationships between variables and dimensions. Research and statistical tests necessary to complete the research. The research reached several conclusions, most notably that the use of modern methodologies for institutional strategic planning, such as the (DCA) methodology, contributes significantly, clearly and tangibly to the development of the performance of different organizations, as it is characterized by its superior ability to diagnose and analyze the information collected in an innovative interactive way and for its various techniques, skills and concepts. It is effective and multiplicity of its outputs that make it distinguished from other methodologies and traditional rigid planning methods. As for the most important recommendations, the higher managements of the various organizations were asked to invest appropriate means and tools and to work according to modern methodologies for strategic planning such as the (DCA) methodology and to rely on it in preparing their strategic plans.
دراسة مستله من بحث الدبلوم العالي في التخطيط الاستراتيجي الموسوم "تشخيص واقع التخطيط الاستراتيجي المؤسسي وفق منهجية DCA: دراسة حالة في مديرية طرق وجسور كربلاء المقدسة"
Keywords: التخطيط الاستراتيجي -- منهجية DCA -- الوحدات الإدارية